Jingle all the way [compact disc, unabridged] - Macomber, Debbie (Random House Audio, 2020)
When a massive snowstorm hits, Everly's mother urges her to come home for Christmas, but she hesitates to return to the life she's worked so hard to escape. Searching for other holiday plans, Everly tasks her assistant with booking her a cruise. Embarking on a weeklong tour of the Amazon guided by charming naturalist Asher Adams, Everly slowly but surely begins to realize that relationships are more important than work, and just might decide to journey home just in time for Christmas Day.